Paper Based Low‐Cost and Portable Ultrasensitive Electroanalytical Devicefor The Detection of Uric Acid in Human Urine. Issue 32 (26th August 2021) - Vishnu, Nandimalla; Sihorwala, Ahmed Z.; Sharma, Chandra S.
Abstract: The electrochemical literature describes a plethora of devices for various applications. Design and development of such paper‐based analytical device(PAD) for sensing applications is paramount of interest. In this work, a PAD was developed using common office‐hold items like paper, pencil, crayons and scotch tape. On a paper, a three‐electrode system was developed by simple drawing with pencils, and the accessible area was confined by creating a hydrophobic barrier using color crayons. The newly developed PAD can hold a low‐dead volume of 25 μL for the analysis and is sealed at the bottom using scotch tape. In our preliminary approach, uric acid (UA), a critical biomarker, was demonstrated as a model analyte for the application of the developed PAD as an electrochemical sensor. The sensor exhibited better analytical performance for UA sensing in a wide range (0.1–1 mM) with appreciable reproducibility, sensitivity (0.3×10 −3  A M −1 ) and selectivity over common interferents (ascorbic acid, urea and glucose). Furthermore, the developed electroanalytical approach was validated by testing the UA in non‐invasive bio‐sample (human urine). Such a cheap, portable, disposable, biocompatible, eco‐friendly and fully‐drawn PAD paves the way for the development of affordable ' lab on paper ' devices for a wide range of bioanalytical applications. Abstract : Office items like paper, crayon, pencil, wax and tape used for development of a cheap, portable, disposable, biocompatible, eco‐friendly and fully‐drawn paper based analytical device as a 'lab on paper' and validated for uric acid detection in human urine sample